Afrikaleidoskop meets ARTE - Senegal: From Paris to Dakar (Afrikaleidoskop meets ARTE, 2024)
For the third time, an event as part of the series "AfriKaleidoskop meets ARTE" took place on March 20th 2024. The Africa Multiple Cluster of Excellence at the University of Bayreuth, in collaboration with the cultural broadcaster ARTE, invited the interested public to a presentation of the documentary "Senegal: From Paris to Dakar" followed by a discussion at the Kulturhaus Neuneinhalb in Bayreuth. Dr Lamine Doumbia, research associate at the Institute for Asian and African Studies at Humboldt University in Berlin, and Dr Ibrahima Sene, research associate at the Chair of History with a focus on African history at UBT, were available for the subsequent discussion. Senegal: From Paris to Dakar - a report by Jean Yves Cauchard, Gaspard Baudry, Sylvain Kasper and Valentin Barrault (24 min.) Six years ago, Ibrahima Sylla, a former cab driver from Paris, founded "Salam Transport", a private bus company that connects Dakar with many cities. Today it is the number 1 in Senegal. Coumba Sow had a good job as a manager in a French bank, but she took a year off to set up "PariSénégal", an agency with which she helps Senegalese French people return to their homeland. Bakary Coly was employed by the French state financial institution Caisse des Dépôts for 15 years. He founded a start-up in Senegal for delivery services with electric motorcycles. Between 2014 and 2019, Senegal recorded a growth rate of 6%, which is interesting for entrepreneurs with good ideas. The pandemic in Europe has also spurred many relocation plans to Africa. The French-Senegalese youth in France and Europe see these opportunities in their parents' homeland. Unlike many young people in Senegal, who are prepared to put their lives on the line for their dream of Europe.